2023
DOI: 10.3390/ani13050944
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetics in Domestic Bovids: A Review

Abstract: The discovery of the Robertsonian translocation (rob) involving cattle chromosomes 1 and 29 and the demonstration of its deleterious effects on fertility focused the interest of many scientific groups on using chromosome banding techniques to reveal chromosome abnormalities and verify their effects on fertility in domestic animals. At the same time, comparative banding studies among various species of domestic or wild animals were found useful for delineating chromosome evolution among species. The advent of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 296 publications
0
5
0
Order By: Relevance
“…Traditionally, FISH and banding technologies have been central in identifying chromosomes involved in chromosomal anomalies [25]. However, both techniques have required high-quality chromosomal preparations, which are only feasible with fresh blood material.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, FISH and banding technologies have been central in identifying chromosomes involved in chromosomal anomalies [25]. However, both techniques have required high-quality chromosomal preparations, which are only feasible with fresh blood material.…”
Section: Discussionmentioning
confidence: 99%
“…[100,101] qPCR Sperm DNA: TL greater in good quality semen samples than in low quality. [102,103] Bos taurus beef Densitometry Breed differences detected.…”
Section: Telomere Research In Livestockmentioning
confidence: 99%
“…The TL of DNA in the semen of Holstein bulls was suggested as a marker for bull semen quality [102,103]. Bulls with "suitable" semen quality had higher volume and motility, increased viability, and a lower incidence of anomalies than bulls in the "unsuitable" category.…”
Section: Dairy Cattlementioning
confidence: 99%
“…Vozdova et al identified a specific chromosomal marker for rob(1;29) that allows detection only in bovine spermatozoa 16 . However, this detection technology involves more complex fluorescence in situ hybridization (FISH) analysis compared to classic cytogenetic methods 17 .…”
Section: Introductionmentioning
confidence: 99%